The importance of preventive physiotherapy in postural changes in older people (Research, Society and Development, 2023)
The objective of the present study was to inform about the importance of physiotherapy in the health of the elderly and the role of the physiotherapist, what are the benefits, the relevance of motor physiotherapy and its importance for the body homeostasis, mental and social health of the elderly. Based on IBGE data, the increase in the elderly population in Brazil is highlighted. The text discusses the fragility associated with aging, focusing on the importance of physiotherapy in preventing falls and improving quality of life. The crucial role of gerontological physiotherapy in preserving the motor and cognitive function of the elderly is highlighted, aiming to delay disabilities. Postural control and physiotherapeutic interventions for postural changes are explored, highlighting aquatic physiotherapy as an option. The text emphasizes the preventive role of physiotherapy in the health of the elderly, addressing functional assessment and different methods, such as the Katz and Lawton scales. Furthermore, it highlights the relevance of the multidisciplinary team and the need for health education. It concludes by highlighting the significant contribution of physiotherapy to promoting a better quality of life, body homeostasis and healthy aging in the elderly population.